Blood Brothers - Roberts, Nora (New York : Jove Books, 2007)
Every seven years, on the seventh day of the seventh month, strange things happen, and three friends--Caleb, Fox, and Gage--must battle against evil with the women who love them by their sides.
Keywords: Friendship; Blessing and cursing; Investigative reporting; Maryland; Romantic suspense novels; Occult fiction